Martensitic ferromagnetism and spin glass behaviour in Ni47Mn36Cr4Sn13 ribbons. (August 2019) - Borgohain, Barsha; Siwach, P.K.; Singh, Nidhi; Awana, V.P.S.; Singh, H.K.
Abstract: Ni47 Mn36 Cr4 Sn13 ribbons were prepared by melt-spinning of the as synthesised bulk alloy. The room temperature structure of the ribbon is dominantly cubic L21 with small admixture of the martensitic orthorhombic phase. The dominance of odd superlattice peak (111) over (200) peak suggests noticeable presence of chemical disorder and hence antisite defects. The temperature dependent resistivity and magnetization measurements unravel the martensitic phase (MP) around ∼360 K in the high temperature austenite phase (AP), while the AP-MP transition occurs at 307 K during cooling and the reverse appears at 328 K in warming cycle. The low field magnetoresistance is rather small and exhibits nonlinear temperature dependence in the low field region. A robust re-entrant ferromagnetic transition whose magnetic moment is almost thrice that of the austenite phase occurs in the martensitic phase. At further lower temperatures, the ferromagnetic transition is succeeded by a re-entrant spin glass (RSG). The analysis of the frequency dispersion of the spin freezing temperature within the Vogel-Fulcher law yields a high value of activation energy (Ea ≈ 50.8 meV) and smaller time constant (τ = 3.28 × 10 −12 s) as compared to usual SG behaviour generally observed in Heusler ribbons. However, alternative analysis in terms of the dynamic scaling law validates the canonical nature of the spin glass and hence appears to be better option for analysing the spin glass states associated with the re-entrant ferromagnetism. Highlights: 'Cr' enhanced austenite-martensite transition. Robust re-entrant ferromagnetism in the martensitic phase. Spin glass with strong interacting spin clusters.